Towards the Development and Validation of a Smartphone-Based Pupillometer for Neuro-Ophthalmological Diseases Screening - Sousa, Ana Isabel (2022)
A special acknowledgment to Compta S.A. team and to the Ophthalmology Department of Hospital Santa Maria for all the support given. Publisher Copyright: © 2021, Springer Nature Switzerland AG.